HUBUNGAN PRESTASI BELAJAR DANKONDISI EKONOMI KELUARGA DENGAN MINAT MELANJUTKAN STUDI S2 MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK MESIN FKIP UNS SEMESTER VIII TAHUN AKADEMIK 2012/2013 - Aziz, Abdul (Jurnal Nosel, 2015)
This research aims at knowing the correlation between the students? achievements and interest to continue the study in post graduate program, the correlation between family?s economic conditions and the students? interest to continue the study in post graduate program, and the correlation between students? achievements and the family?s economic conditions in interest to continue the study in post graduate program for students of Mechanical Engineering eigth semester 2012/2013 academic year. This research was conducted at the campus V FKIP UNS Pabelan, the researcher used quantitative descriptive method. The population of this research was students of mechanical engineering department eight semester 2012/2013 academic year, they were 56 students. The samples was taken by using a random sampling technique that involving 48 students. The instruments used in this study were the distribution questionnaires. The test of instrument validation applied a product moment formula and a construct validity formula. The test of instrument reliability applied an Alpha Cronbach formula. Test requirements analysis covered test of normality, linearity and multicollinearity. Data analysis techniques used analysis of product moment correlation, partial correlation and multiple regression tests. The results of the analysis show that: (1) there is a positive relation between students? achievement results and the students? interest for continuing the study at post graduate program (ry1 of 0,392 > rt amount 0,284 at a significance level of 5%). (2) There is a negative relation between the economic conditions of families with the interest for continuing the study in post graduate program (ry2 of -0,232 < 0 < rt of 0,284 at a significance level of 5%). Coefficient of determinant is 0,296. The results show that both students? achievement results and the economic conditions of families give significant contribution to the interest for continuing the study in post graduate program although the values are different.